Analysis of the Role of Aviation Security and Safety Supervision of The Aviation Security Unit (AVSEC) at Sultan Babullah Airport, Ternate - M Nur, Fachrizky Wardana; Awan, Awan (CV. Rayyan Dwi Bharata, 2024)
Security and safety are crucial factors in aviation activities, considering the sensitivity of air transportation that requires certainty of safety at all times. The success of the duties and responsibilities of the Aviation Security unit is measured by their ability to optimize their supervisory role, thus creating safe and secure conditions, in accordance with applicable regulations and free from unlawful acts at an airport. This study aims to determine the supervision of the Aviation Security unit on flight security and safety at Sultan Babullah Ternate Airport and the supporting equipment used in its supervision. This study uses a descriptive qualitative approach. The data used are primary and secondary data. Primary data is obtained from observation and interviews, while secondary data comes from SOP, literature studies and photographs related to the problems studied. The data analysis techniques used are data reduction, data presentation and drawing conclusions. The research time is in August - September 2023. The results of this study indicate that the role of the Aviation Security unit supervision at Sultan Babullah Ternate Airport has been carried out properly according to the Standard Operating Procedure (SOP) starting from checking passenger travel documents (identity), passenger body screening (body search), passenger baggage screening, monitoring the movement of everyone in the terminal, conducting routine patrols in all areas of the airport including the perimeter fence. Supervision with competent personnel who have been licensed. Avsec unit supervision aims to prevent unlawful acts and maintain the security and safety of flight activities. Supporting equipment in carrying out supervision is an X-Ray machine, HHMD (Hand Held Metal Detector), WTMD (Walk Through Metal Detector), EDS (Explosive Detection System), patrol vehicles and Closed Circuit Television (CCTV).